1977
DOI: 10.1007/bf00414821
|View full text |Cite
|
Sign up to set email alerts
|

Vertr�glichkeitsuntersuchungen von Holz im Knochengewebe

Abstract: Alcohol-extracted and sterilised cylinders of ash- and birchwood were implanted into the tibia of rabbits. The selection criteria of these two wood species were thoroughly described. 28 implants were evaluated after 3, 5, 14 and 32 weeks using undecalcified microtome sections and ground sections employing polychromatic sequential-labelling and microradiography. In spite of a foreign-body-tissue reaction new bone is formed around the implants and within the pores of the wood as well. Both wood species therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…While in the studies of Kristen et al (1977Kristen et al ( , 1979 direct bone contacts to wood surfaces could be shown, no direct bone contact, but only a foreign body response was observed at the cellulose interfaces in your referenced study of Gross et al (1992). Thus, the Gross et al (1992) cellulose material, as well as the PLA-PGA materials, are not "osteoconductive" in my understanding.…”
Section: H Plenkmentioning
confidence: 92%
See 1 more Smart Citation
“…While in the studies of Kristen et al (1977Kristen et al ( , 1979 direct bone contacts to wood surfaces could be shown, no direct bone contact, but only a foreign body response was observed at the cellulose interfaces in your referenced study of Gross et al (1992). Thus, the Gross et al (1992) cellulose material, as well as the PLA-PGA materials, are not "osteoconductive" in my understanding.…”
Section: H Plenkmentioning
confidence: 92%
“…Were the authors aware of the studies by Kristen et al (1977Kristen et al ( , 1978, and later by the people in Leiden (Li et al, 1997a,b) on bone reactions to wood, and that mineralization occurs naturally in several species of wood? Authors: We are well aware of those studies and they are thoroughly discussed in our previous papers concerning mineralization studies of cellulose in SBF (references are provided in the introduction).…”
Section: H Plenkmentioning
confidence: 99%